Pt-Ni Aerogels as Unsupported Electrocatalysts for the Oxygen Reduction Reaction. Issue 9 (1st January 2016) - Henning, Sebastian; Kühn, Laura; Herranz, Juan; Durst, Julien; Binninger, Tobias; Nachtegaal, Maarten; Werheid, Matthias; Liu, Wei; Adam, Marion; Kaskel, Stefan; Eychmüller, Alexander; Schmidt, Thomas J.
Abstract : The commercial feasibility of polymer electrolyte fuel cells (PEFCs) passes by the development of Pt-based, O2 -reduction catalysts with greater activities and/or lower Pt-contents, as well as an improved stability. In an effort to tackle these requirements, unsupported bimetallic Pt-Ni nanoparticles (NPs) interconnected in the shape of nanochain networks (aerogels) were synthesized using a simple one-step reduction and gel formation process in aqueous solution. The products of this novel synthetic route were characterized by X-ray absorption spectroscopy to elucidate the materials' structure. Using electrochemical experiments, we probed the surface composition of the as-synthesized aerogels and of equivalent materials exposed to acid, and concluded that a Ni-(hydr)oxide side phase is present in the aerogel with a larger Ni-concentration. Regardless of this initial surface composition, the Pt-Ni aerogels feature a ≈3-fold increase of surface-specific ORR activity when compared to a commercial platinum-on-carbon catalyst, reaching the mass-specific requirement for application in automotive PEFCs.